Autocad 2000 : - Frey, David (Sybex, 1999)
AutoCAD 2000: No Experience Required is your step-by-step introduction to the latest version of AutoCAD, the computer drafting and design program that has become the industry standard in architecture, landscaping, engineering, and construction. Inside, practical examples and straightforward explanations show you exactly what you need to know to create a project -- and will help you master every essential AutoCAD feature.